CRLF1 Is a Key Regulator in the Ligamentum Flavum Hypertrophy - Zheng, Zhenyu; Ao, Xiang; Li, Peng; Lian, Zhengnan; Jiang, Tao; Zhang, Zhongmin; Wang, Liang (Frontiers in Cell and Developmental Biology, 2020)
Hypertrophy of the ligamentum flavum (HLF) is one of the common causes of lumbar spinal stenosis (LSS). The key molecules and mechanisms responsible for HLF remain unclear. Here, we used an integrated transcriptome and proteomics analysis of human ligamentum flavum (LF), and subsequent immunohistochemistry and real-time PCR assays, to show upregulation of CRLF1 to be the dominant response to HLF. TGF-β1 significantly increased mRNA expression of CRLF1 through SMAD3 pathway. CRLF1 enhanced LF fibrosis via ERK signalling pathway at the post-transcriptional level and was required for the pro-fibrotic effect of TGF-β1. Knockdown of CRLF1 was shown here to reduce fibrosis caused by inflammatory cytokines and mechanical stress. Furthermore, we found that bipedal standing posture can cause HLF and upregulation of CRLF1 expression in mice LF. Overexpression of CRLF1 was indicated to cause HLF in vivo, whereas CRLF1 knockdown impeded the formation of HLF in bipedal standing mice. These results revealed a crucial role of CRLF1 in LF hypertrophy. We propose that inhibition of CRLF1 is a potential therapeutic strategy to treat HLF.